Age‐dependent effects of predation risk on reproductive success in a freshwater snail. (24th September 2015) - Auld, Josh R.; Houser, Ryan
<x xml:space="preserve">Abstract</x> Reproductive performance is often age‐dependent, showing patterns of improvement and/or senescence as well as trade‐offs with other traits throughout the lifespan. High levels of extrinsic mortality (e.g., from predators) have been shown to sometimes, but not always, select for accelerated actuarial senescence in nature and in the lab. Here, we explore the inductive (i.e., plastic) effects of predation risk (i.e., nonlethal exposure to chemical cues from predators) on the reproductive success of freshwater snails (Physa acuta). Snails were reared either in the presence or absence of chemical cues from predatory crayfish and mated early in life or late in life (a 2 × 2 factorial design); we measured egg hatching and early post‐hatching survival of their offspring. Both age and predation risk reduced reproductive success, illustrating that predation risk can have a cross‐generational effect on the early survival of juveniles. Further, the decline in reproductive success was over three times faster under predation risk compared to the no‐predator treatment, an effect that stemmed from a disproportionate, negative effect of predation risk on the post‐hatching survival instead of hatching rate. We discuss our results in terms of a hypothesized consequence of elevated stress hormone levels.